REPRESENTASI GIRL POWER PADA LAGU “TALLY” OLEH BLACKPINK - Fatonah, Astri Amaliah; Handayani, Wiwik Retno (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2024)
A patriarchal culture dominated the representation of social reality, resulting in women's victimization. However, now the media is highlighting women in terms of educational achievements, so the existence of independent women is increasing. This research aims to discuss the representation of Girl Power shown in the video clip and lyrics of the song "Tally" by Blackpink. The research is based on qualitative methods with John Fiske's theoretical concepts of semiotics and Sara Mills' critical discourse analysis. The study results show that the video clip and lyrics of the song "Tally" by Blackpink represent Girl Power. The women depicted by Blackpink are strong. The ideology displayed stands out and is by the spirit of postfeminism that women's bodies cannot be used as objects and cannot be owned by men. Women's bodies and feelings can only be controlled by women without men's interference.